Agile Governance Dalam Meningkatkan Layanan Kegawatdaruratan Cirebon Siaga 112 di Kota Cirebon - Firmansyah, Alya Nisrina; Munajat, Mas Dadang Enjat (Kolaborasi : Jurnal Administrasi Publik, 2025)
In order to improve the quality of public services, the Cirebon City Government has taken agile steps to provide effective and efficient emergency services for the community through the Cirebon Siaga 112 service. Cirebon Siaga 112 is an adoption of the Single Number of Emergency Calls (NTPD) 112 service concept that provides integrated complaint services to facilitate the handling of emergency conditions with a single number 112 that can be accessed by the public 24 hours without a call fee. This study aims to describe the application of Agile Governance in the implementation of Cirebon Siaga 112 public services in Cirebon City, using the Agile Governance theory proposed by Luna et al. (2015). This research uses a qualitative approach, for data collection techniques carried out are interviews, observation and documentation. The results showed that the implementation of Cirebon Siaga 112 in Cirebon City has been quite good in applying the principles of Agile Governance to improve the quality of public services that are more effective and efficient. However, the Human Focused principle still needs improvement related to community participation. This recommendation aims to optimize the application of Agile Governance principles in the implementation of Cirebon Siaga 112 public services in Cirebon City and provide implications for other regions on the importance of adopting technology-based services and involving the community in developing public service innovations.